Investigations to increase the failure load for joints in glass epoxy composites. (March 2019) - Singh, Kulwinder; Saini, JS; Bhunia, H; Singh, Jaspreet
The present work aims to increase failure loads of pin joints through nanofillers and metal inserts. Pin joints were prepared from woven glass fiber-reinforced laminates with nanoclay as filler material along with metal inserts fitted in holes. To investigate the effect of nanoclay content, 1–5 wt.% of nanoclay was mixed in epoxy. The increase in tensile strength up to 3 wt.% of nanoclay was observed which was due to increase in the specific surface area of the nanocomposite material. Dispersed nanoclay filler particles act as mechanical interlocking between fiber and epoxy matrix which creates a high friction coefficient. The optimal nanoclay content of 3 wt.% was finally used to prepare nanocomposite laminates. The geometric parameters, i.e. edge distance to hole diameter (E/D) ratio and width to hole diameter (W/D) ratio were varied from 2 to 5 and 3 to 6, respectively. Progressive damage analysis along with Hashin failure criteria was performed to predict failure loads and failure modes in pin joints, numerically. Metal inserts reduced the stress concentration around the hole and redistributed stresses at the pin/hole interface, which eventually increased the ultimate failure load of the joint.